Design of modular concrete heliostats using symmetry reduction methods. Issue 4 (8th October 2020) - Forman, Patrick; Penkert, Sebastian; Mark, Peter; Schnell, Jürgen
Abstract: In Concentrated Solar Power (CSP) plants the incident solar radiation is focused onto a receiver by means of collectors. A fluid is heated up and in a downstream power block electricity is generated. In point‐focusing solar towers, the solar concentration is achieved by so‐called heliostats that are arranged to a solar field. In this contribution, the development of concrete heliostats with circular shapes and an aperture area of 30 m 2 is presented. A high‐performance concrete with high tensile and compressive strength values is used. The circular structure is dissolved into identical but symmetrically reduced modules derived from system reduction methods. For designing, the tensile strength of the concrete is restrictive to ensure linear‐elastic material behavior and to avoid softening by cracking. After dimensioning, the derived equivalent plate is converted into strut‐like structures possessing equal stiffnesses with respect to the partial module size. These modules are circularly post‐tensioned to form a heliostat. Numerical investigations of the modules prove their accuracy. A full solar concentration, that is, the reflected solar radiation is completely focused on the receiver, is achieved. Due to the multitude of modules within a solar field, serial production with integrated quality control is recommended.